Potential use of entomopathogenic and mycoparasitic fungi against powdery mildew in aquaponics - Folorunso, Ewumi Azeez; Bohatá, Andrea; Kavkova, Miloslava; Gebauer, Radek; Mraz, Jan (Frontiers in Marine Science, 2022)
Aquaponics has the potential to produce sustainable and accessible quality food through the integration of hydroponics and aquaculture. Plants take up dissolved nutrients in fish wastewater, allowing water reuse for fish. However, the simultaneous presence of fish and plants in the same water loop has made phytosanitary treatments of diseases such as powdery mildew problematic due to risks of toxicity for fish and beneficial bacteria, limiting its commercialization. Entomopathogenic and mycoparasitic fungi have been identified as safe biological control agents for a broad range of pests. This study aimed to investigate the efficacy of entomopathogenic fungi, Lecanicillium attenuatum (LLA), Isaria fumosorosea (IFR), and mycoparasitic fungus Trichoderma virens (TVI) against Podosphaera xanthii. Also, we investigated the possible harmful effects of the three fungal biocontrol agents in aquaponics by inoculating them in aquaponics water and monitoring their survival and growth. The findings showed that the three biocontrol agents significantly suppressed the powdery mildew at 107 CFU/ml concentration. Under greenhouse conditions (65-73% relative humidity (RH)), a significant disease reduction percentage of 85% was recorded in L. attenuatum-pretreated leaves. IFR-treated leaves had the least AUDPC (area under disease progress curve) of ~434.2 and disease severity of 32% under 65-73% RH. In addition, L. attenuatum spores were the most persistent on the leaves, the spores population increased to 9.54 × 103 CFUmm-2 from the initial 7.3 CFUmm-2 under 65-73%. In contrast, in hydroponics water, the LLA, IFR, and TVI spores significantly reduced by more than 99% after 96 hrs. Initial spore concentrations of LLA of 107 CFU/ml spores were reduced to 4 x 103 CFU after 96 hrs. Though the results from this study were intended for aquaponics systems, relevance of the results to other cultivation systems are discussed.